OCCURRENCE TYPES AND CHARACTERISTICS OF NON-LITERARY LEXICAL ELEMENTS IN ANONYMOUS LETTERS - Sevara Yoqubova (Galaxy International Interdisciplinary Research Journal, 2024)
In linguistics, non-literary lexical elements are studied in the lexicon with a limited scope of use. A number of studies have been conducted on the linguistic nature of the lexemes of this group. The issue of the concept of non-literary lexical element, its role and importance is relevant in linguistic expertise. In the article, the non-literary lexical element, its importance, as well as factors related to its occurrence in speech are shown on the basis of examples.